Correction: Recent developments of a co-immobilized laccase–mediator system: a review. Issue 25 (27th May 2022) - Gu, Yaohua; Yuan, Lin; Jia, Leina; Xue, Ping; Yao, Huiqin
Abstract : Correction for 'Recent developments of a co-immobilized laccase–mediator system: a review' by Yaohua Gu et al., RSC Adv., 2021, 11, 29498–29506, ; https://doi.org/10.1039/D1RA05104K .